2019
DOI: 10.3171/2019.2.peds18384
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials for pediatric traumatic brain injury: definition of insanity?

Abstract: Traumatic brain injury (TBI) is a leading cause of morbidity and mortality in children both in the United States and throughout the world. Despite valiant efforts and multiple clinical trials completed over the last few decades, there are no high-level recommendations for pediatric TBI available in current guidelines. In this review, the authors explore key findings from the major pediatric clinical trials in children with TBI that have shaped present-day recommendations and the insights gained from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…High-quality research in ICP monitoring and regulation in severe pediatric TBI is still limited. Limitations may be due to the heterogeneity in pathology, patient populations (as previously mentioned), treatment algorithms including threshold values and sensitivity and specificity in outcome measurements (8). Further research must be conducted for future guidelines to provide level I or level II recommendations.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…High-quality research in ICP monitoring and regulation in severe pediatric TBI is still limited. Limitations may be due to the heterogeneity in pathology, patient populations (as previously mentioned), treatment algorithms including threshold values and sensitivity and specificity in outcome measurements (8). Further research must be conducted for future guidelines to provide level I or level II recommendations.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Further research must be conducted for future guidelines to provide level I or level II recommendations. Studies can still add evidence by examining smaller, but more homogenous patient groups (8), as such studies can also be collected into meta-analysis protocols.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The answer lies in the reality of 500 completed, suspended, withdrawn, or terminated clinical trials for traumatic brain injury, of which 127 have been conducted in the pediatric population. As was recently and aptly pointed out by Appavu et al, every trial has failed to produce high-quality evidence for the treatment of pediatric TBI [184]. A common theme across these trials is the targeting of a singular mechanism of secondary injury and use of a small number of biomarkers to evaluate success.…”
Section: Conclusion and Future Directions For Research And Therapymentioning
confidence: 99%
“…Children sustaining complicated mild TBI have been found to be more vulnerable to developing mild neuropsychological dysfunctions that persist chronically, when compared to adults [ 4 ]. Despite the implications of these findings, both pre-clinical [ 5 ] and clinical [ 6 ] research addressing pediatric TBI is limited. A 2018 systematic review found that despite increasing research, gaps remain in the diagnosis, prognosis, and management of pediatric mild TBI [ 7 ].…”
Section: Introductionmentioning
confidence: 99%